دراسة قصيدة »أول األرض هذا« لـ "علي جعفر العالق" يف ضوء منهج التحليل النقدي للخطاب. - حسني الياسي مفرد; زينب قامسي اصل (Arabic Language & Literature (1735-9767), 2023)
With new critical tendencies, especially after the emergence of critical discourse analysis, text analysis methods surpassed the structure framework Analyzing texts and discourses has become an, organized and deep index. Examining the address with this new critical method is conducted at various levels. text analysis is a systematic, deep and comprehensive analysis that relies on the context and atmosphere of text and discourse production. Analyzing the discourse and focusing on it, examining the ideological tendency of the speech and its relationship with the power relations or the role of the address in changing these relations are among the chief concepts in critical discourse analysis. Lacla and Mouffe's model is one of the most important methods of critical discourse analysis that makes an effort to investigate the movement of different signifiers within the discourse. It also examines the deep connection between the elements, topics, and components of discourse and central and floating signifiers. Also, the ideological tendency of speech, the process of highlighting and marginalization, and discourse conflict are among the fundamental concepts raised in this critical approach. This research aims to study the ode "This is the Beginning of the Earth" by Ja'far alAllaq, one of the prominent poets of Iraq, with the critical discourse analysis approach of Lacla and Mouffe. The research results suggest that Palestine is the central signifier of this poetic discourse and that there is a discourse conflict at different levels, with the conflict between the resistance discourse and the discourse of normalizing relations with Israel. This poetic discourse consists of floating signifiers that reinforce the central signifier. By focusing on the significant signifier, the poet accentuates the concept with discourse instruments such as repeating the word Palestine and emphasizing the certainty of the occupier's departure and freedom of Palestine. In this poetic discourse, the poet seeks to marginalize the occupier and the current Arab address by mockery. The poet condemns the current government in his poetic speech. The presence of a set of discourse signifiers and symbols that carry the task of reassuring and hope in the field of conflict injects specific knowledge and awareness to establish a promising future; Moreover, by using intertextuality, it seeks to strengthen the hegemony of discourse and reinforce the central signifier to create a state of desirable tendency.